Hybrid Transcriptional Regulators for the Screening of Target DNA Motifs in Organohalide-Respiring Bacteria - Willemin, Mathilde Stéphanie; Vingerhoets, Marie; Holliger, Christof; Maillard, Julien (Frontiers in Microbiology, 2020)
The bioremediation of persistent organohalide molecules under anoxic conditions mostly relies on the bacterial process called organohalide respiration (OHR). Organohalide-respiring bacteria (OHRB) are phylogenetically diverse anaerobic bacteria that share the capacity to use organohalides as terminal electron acceptors in an energy-conserving process. The reductive dehalogenase (rdh) gene clusters encode for proteins specialised in the respiration of one or a limited number of organohalides. One particular OHRB may harbour up to several dozens of rdh gene clusters suggesting a wide potential for bioremediation. To avoid wasting energy in producing unnecessary proteins, rdh gene clusters often include a transcriptional regulator. In organohalide-respiring Firmicutes, RdhK is a dedicated transcriptional regulator of OHR and represents a subfamily of proteins among the CRP/FNR superfamily of regulators. RdhK proteins are composed of an effector-binding domain (EBD) which recognises a given organohalide and subsequently controls the interaction of its C-terminal DNA-binding domain (DBD) with a DNA motif (referred to as dehalobox, or DB) located in the promoter region of the target rdh genes. The two binding partners (i.e. an organohalide molecule and a DB sequence) of RdhK proteins are interdependent which impairs the exploration of OHR regulatory networks. Here, we propose a strategy relying on hybrid proteins to efficiently screen the DNA target of a single RdhK protein without prior knowledge on its effector. To demonstrate the potential of the method, two hybrids with alternative fusion points were designed based on RdhK6 EBD and RdhK1 DBD from Desulfitobacterium hafniense. Electrophoretic mobility shift assay was performed with purified hybrids along with the parental proteins and their binding properties were further tested in vivo through a β-galactosidase reporter assay. Along with revealing new RdhK6 features, we show that both hybrids resulted in active regulatory proteins with distinct binding patterns. While Hybrid A was less specific for the DNA motif, Hybrid B successfully mimicked the binding behaviour of the parental proteins and thus represents a promising template for the design of new RdhK hybrids to screen yet uncharacterised RdhK proteins and also possibly other members of the CRP/FNR superfamily.